Communication and Information Technologies Annual [New] Media Cultures. - Laura Robinson; Jeremy Schulz; Shelia R. Cotten; Timothy Hale; Apryl Williams (Bingley, U.K. : Emerald, 2016)
Sponsored by the Communication and Information Technologies Section of the American Sociological Association, this volume examines wide-ranging aspects of culture, communication, and [new] media broadly defined. Themes include the interplay between [new] media and any of the following: culture, communication, technology, convergence, the arts, cultural production, and cultural change in the digital age. Contributions shed light on emergent phenomena that sociologists, particularly those studying media or communication, culture scholars will find intriguing.
On Violating Ones Own Privacy: N-adic Utterances and Inadvertent Disclosures in Online Venues Youve been catfished: an analysis of postemotionalism in reality television and audience response on Twitter Ana Campos-Holland,Brooke Dinsmore,Jasmine Kelekay Gabe Ignatow,Nicholas Evangelopoulos,Konstantinos Zougris
Keywords: Social Sciences; Social Science -- Media Studies; Media studies; Social interaction; Sociology